A Model of International Development Cooperation: The Case of Slovenia - Rogelj, Janez; Bojnec, Štefan; Logožar, Klavdij (Naše gospodarstvo/Our economy, 2023)
Development aid, one of the most important mechanisms for the redistribution of global wealth, represents financial flows with economic growth and social improvement as their primary objective. Recently, international development cooperation has been in the process of change that requires the involvement of new actors, the use of new instruments, and expanding the fields of work. In this article, the authors introduce the Slovenian model of international development cooperation, emphasising the criteria for deciding the direction of development cooperation. The criteria are clear interest of the beneficiary state, content priority fields, and geographical priority areas. The authors also discuss Slovenia's active collaboration with the United Nations Industrial Development Organization in international development cooperation. Special attention is given to three successful development projects in Africa that Slovenia recently financed. All three selected projects are based on principles of sustainable development and were realized in Kenya, Tanzania, and Uganda.